Dampak Status Gizi, Pola Hidup Sehat dan Aktivitas Fisik terhadap Kebugaran Jasmani pada Siswa Sekolah Dasar Pasar Ikan Sidoarjo - Bayu Samudera, Firda Dewinta; Wahjuni, Endang Sri; Hidayat, Taufiq (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Physical Education, Sports and Health (PJOK) includes general education which aims to improve the quality of life, both physical and spiritual, by carrying out physical activities and sports. In general, nutritional status, healthy lifestyle and physical activity have important goals for health and physical fitness. This research aims to determine the impact of nutritional status, healthy lifestyle and physical activity which have a significant influence on physical fitness in elementary school students in grades IV, V and VI. This research uses a Quantitative Approach with a Chi-Square Descriptive Research Design, Data Requirements Test, Multicollinearity Test, Heteroscedasticity Test and Multiple Linear Regression as well as Hypothesis Testing. Data collection was obtained through measuring nutritional status using BMI/U calculations, filling out questionnaires in healthy lifestyle research using PHBS (Clean and Healthy Lifestyle), filling out physical activity questionnaires, and physical tests using the Pacer test. The conclusion of this research is that there is a significant relationship between the three independent variables and the dependent variable with a simultaneous F test value of Sig. 0.002 < 0.05, then there is a significant relationship with the physical fitness endurance variable. Meanwhile, the partial T test results of the three independent variables are the physical activity variable which significantly influences physical fitness with the Sig value. 0.001 < 0.05, and the nutritional status variable, the healthy lifestyle variable obtained results that did not significantly influence physical fitness with a result value of Sig. 0.916 and Sig.0.188 > 0.05.